Cephalometric Evaluation of Craniofacial Pattern of Nepalese Patients with Class III Malocclusion - Parajuli, Umesh; Mishra, Praveen; Bhattarai, Prakash; Bajracharya, Manish; Paudel, Keshab Raj; Tuladhar, Sapna Laxmi (Orthodontic Journal of Nepal, 2012)
Objective: To find out the differences in craniofacial pattern between Class lll malocclusion and normal occlusion in Nepalese population. Materials and Methods: Lateral cephalogram of 30 patients with Class lll malocclusion (11 male and 19 female; mean age, 17.27 ±3.88 years) and 30 patients with normal occlusion (15 males and 15 females; mean age: 19.03 ± 4.94 years) were analyzed for various linear and angular measurements. The variables between the two groups were compared using independent t - test. Results: The base angle N-S-Ar was significantly smaller ( < 0.05) in Class lll group. The relative position of the maxilla in sagittal relation as indicated by angle of convexity (N-A-Pog) and A to N perpendicular was significantly retrusive in Class lll group ( < 0.05). The length of the maxilla was significantly reduced in Class lll group ( <0.01). The relative sagittal position of the mandible was significant protrusive in Class lll group as indicated by SNB (P< 0.01), facial angle (FH to N Pog) ( <0.05) and N perpendicular to Pog ( <0.001). The upper incisors were proclined and positioned anteriorly ( <0.01) in Class lll group while the lower incisors were retroclined ( <0.05). The upper lip in Class lll was retrusive ( < 0.05) relative to Ricketts esthetic plane and the nasolabial angle was significantly decreased in Class lll groups ( < 0.01). Conclusion: There are significant differences in craniofacial pattern in Class lll Nepalese population as compared to normal Nepalese population.